2021
DOI: 10.6065/apem.2040240.120
|View full text |Cite
|
Sign up to set email alerts
|

Patients with disorders of sex development

Abstract: Disorders of sex development (DSDs) are a genetically and clinically heterogeneous group of congenital conditions of the urogenital tract and reproductive system. Time and spatially controlled transcription factors, signal molecules, and an array of different hormones are involved in the development of sex characteristics, and variations in their pathways and actions are associated with DSD. These conditions may be caused by numerical or structural variations in sex chromosomes as well as autosomes, variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In pediatric cases, androgen excess is the commonly observed presentation, followed by Cushing syndrome or a combination of both [4]. Therefore, it is important to consider multiple possibilities in the differential diagnosis of virilization, including androgen-secreting tumors and congenital adrenal hyperplasia [6,7]. Cushing syndrome tends to be more prevalent in older age groups [4].…”
Section: Adrenocortical Tumorsmentioning
confidence: 99%
“…In pediatric cases, androgen excess is the commonly observed presentation, followed by Cushing syndrome or a combination of both [4]. Therefore, it is important to consider multiple possibilities in the differential diagnosis of virilization, including androgen-secreting tumors and congenital adrenal hyperplasia [6,7]. Cushing syndrome tends to be more prevalent in older age groups [4].…”
Section: Adrenocortical Tumorsmentioning
confidence: 99%
“…Biomedical research has shown the existence of a variety of groups showing variation in bodily form or genetic makeup: XY females, and babies with ambiguous genitals-indeed a range of intersex conditions, some of which may not be identified before adolescence. 25 Undoubtedly, the biological capacity to be a father is often understood to signify masculinity, but it is in fact far from universal.…”
Section: Problems With Applying the Cur-rent Definitions To Men's Hea...mentioning
confidence: 99%
“…3) CHH is one of the few treatable diseases of male infertility, although men with primary testicular dysfunction show irreversibly diminished spermatogenic capacity. [4][5][6] The approach to CHH treatment is determined by goals such as developing only virilization or inducing fertility. In this review, we describe therapeutic options from different perspectives.…”
Section: Introductionmentioning
confidence: 99%